Penyusunan Kisi-kisi Evaluasi Pembelajaran Ranah Kognitif - -, imroatun (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2021)
Professional teachers are required to be able to master 14 teacher competencies. One of the teacher competencies is teacher pedagogical competence which is the teacher's ability to master the characteristics of students, master the theory of learning and educational principles of learning, curriculum development, educational learning activities, development of potential students, communication with students, research and evaluation. Learning evaluation plays an important role in determining the success of learning. The ability of teachers to prepare learning evaluation tools at this time, is still not as expected. Part of the teacher still has difficulty in arranging learning tools, especially in the preparation of a grid which is a reference or guidelines in preparing questions. The results of research conducted by interviewing, observing and studying documents, on writing a grid for the evaluation of learning in the cognitive domain, show that the teacher still experiences some problems in arranging the lattice. The ability of the teacher in arranging the grid format by including the level / level difficulty (27%), conformity of the formulation of indicators (55%), conformity of KD with indicators (18%), conformity of KKO with the level / level of material being measured (18%). Based on the results of this study, it is necessary to increase the ability of teachers in the preparation of question grids, which are an important part of the preparation of learning evaluation tools.